OPTIMASI PROSES PENYANGRAIAN KAKAO BERBASIS TEKNOLOGI MINDSPHERE DI UGM COCOA TEACHING AND LEARNING INDUSTRY, BATANG, JAWA TENGAH - Kusuma, Enas Dhuhri (RISTEK : Jurnal Riset, Inovasi dan Teknologi Kabupaten Batang, 2024)
The roasting process is one part of cocoa bean processing that determines the quality of the final processed product. In the roasting process, the water content in the cocoa beans is removed and dried. The roasting process also develops the cocoa beans to obtain a distinctive aroma and color that meets standards. Good roasting results require optimal roasting temperature and time. This article explains the optimization of temperature settings at certain roasting times based on roasting data such as roasting capacity, water content, pH, bean type and so on. Data is obtained from real-time recording using Mindsphere technology at CTLI and quality control observations. The data mining method will be used to find the optimal roasting temperature and duration. Temperature is used as the target variable in this article. Temperature is used as the target variable in this article. The data mining algorithm tested in this article is Support Vector Regression (SVR). The performance of the algorithm is then measured by regression standards such as Mean Absolute Percent Error (MAPE) and Root Mean Squared Error (RMSE).